First Case of Nodular Localized Primary Cutaneous Amyloidosis Treated With Bortezomib and Dexamethasone - Noman Ahmed Jang Khan MD; Emma Nellhaus MD; Doreen Griswold MD; Muhammad Omer Jamil MD (SAGE Publishing, 2021)
Nodular localized cutaneous amyloidosis is a rare form of cutaneous amyloidosis and is characterized by an extracellular deposition of insoluble amyloid fibrils which are either primarily cutaneous or a manifestation of an underlying systemic amyloidosis. Biopsy of the lesion is mandatory for the diagnosis, and histopathology shows diffuse amyloid deposits with plasmacytic infiltration. Apple-green birefringence characteristic of amyloidosis is observed when stained with Congo red and viewed under polarized light. Amyloid subtyping is done with laser microdissection followed by mass spectrometry. Majority of these lesions do not require any treatment but surgical excision, shave excision, laser therapy, and radiotherapy can be considered for symptomatic nodular localized primary cutaneous amyloidosis (NLPCA). We present a case of recurrent NLPCA in a 64-year-old woman who was treated with bortezomib and dexamethasone after failing several local therapies with excellent response.